1973
DOI: 10.2118/73-02-05
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Natural Convection In Gas, Oil And Water Reservoirs

Abstract: Natural convection in a fluid layer is a phenomenon which has been the topic of numerous studies. A similar phenomenon has been observed in porous media. In the first part of this paper we review some recent theoretical and experimental studies which allow a better understanding of some quantitative aspects of natural convection in porous media. This review is confined to the case in which compressibility effects are negligible as compared to thermal expansion effects and where the porous layer is homogeneous.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Blanchard and Sharp (1985) presented graphs (reproduced in Sharp et al 1988) that show the critical permeability necessary for the onset of free convection for selected layer thickness and geothermal gradients. Following Aziz et al (1973), they also presented evidence in the form of areal patterns of ground water temperature to support the existence of convection cells in thick sandstone units in the Gulf Coast basin under normal geothermal gradients.…”
Section: Basic Theorymentioning
confidence: 90%
“…Blanchard and Sharp (1985) presented graphs (reproduced in Sharp et al 1988) that show the critical permeability necessary for the onset of free convection for selected layer thickness and geothermal gradients. Following Aziz et al (1973), they also presented evidence in the form of areal patterns of ground water temperature to support the existence of convection cells in thick sandstone units in the Gulf Coast basin under normal geothermal gradients.…”
Section: Basic Theorymentioning
confidence: 90%
“…Natural convection in porous media (Nield and Bejan 2006) has applications in diverse fields including carbon dioxide capture and storage (CCS) (Green and Ennis-King 2013;Huppert Neufeld 2014;Lindeberg and Wessel-Berg 1997;Riaz and Cinar 2014;Islam et al, 2014), petroleum engineering (Aziz et al 1973), geothermal energy recovery (Barvier 2002;Henley and Ellis 1983;Oldenburg and Pruess 1998), and groundwater systems. (Herbert et al 1988;Huyakorn et al 1987;Oostrom et al 1992;Simmons et al 2001; Van et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, at early times or for very thick systems, although the vicinity of the heat source is dominated by convection, overall heat transfer is predominantly conduction. Experimental and complex numerical studies reported similar conclusions, even in dipping systems (Aziz et al, 1973;Holst and Aziz, 1972). Aziz et al (1968) carried out 2D simulations for free convection in a bottom-heated model, rigorously described with the conservation equations and an equation-of-state.…”
Section: Figmentioning
confidence: 83%
“…When the vertical component of the temperature gradient and gravity are in the same direction, as implied in Fig. 1, induced thermal convective motion has been shown to increase the vertical heat transfer (Aziz et al, 1973;Aziz et al, 1968), resulting in a higher Nusselt number (Aziz et al, 1973).…”
Section: Assessing Relative Influence Of Convectionmentioning
confidence: 97%
See 1 more Smart Citation